Теоретичне дослідження небезпек, загроз та ризиків в економічній безпеці підприємства - Архипенко, Т. А.; Іванова, М. І.; Arkhypenko, T. A.; Ivanova, M. I. (Видавництво Львівської політехніки, 2023)
Висвітлено теоретичне дослідження й узагальнено визначення сутності небезпеки, загроз і ризику та з’ясовано їх місце в економічній безпеці підприємства. Схематично наведено взаємозалежність зазначених категорій, які корелюють між собою. Використано метод систематизації для виявлення детермінуючих ознак та метод групування для уточнення концептуальних підходів. Мета роботи полягає в уточненні категоріального апарату цих визначень у контексті економічної безпеки підприємств для успішної діяльності суб’єктів господарювання у мінливих непередбачуваних умовах. У результаті аналізу виявлено наявність процесу формування термінології, поглиблення наукового обґрунтування визначень дефініцій “небезпека”, “загроза” та “ризик”.

This article provides a theoretical study and generalization of the definition of the essence of danger, threat and risk in the economic security of an enterprise. The presence of danger creates a system of organizational and economic actions to protect the enterprise from the onset of risk. Schematically, the interdependence of these categories is shown which correlate with each other. At the same time, the systematization method was used to identify deterministic features and the grouping method to clarify conceptual approaches. The aim of the work is to clarify the categorical apparatus of hazards threats and risks in the context of economic security of enterprises for the successful operation of business entities in modern conditions. In the course of the theoretical study, it was possible to systematize the determining signs of danger from the point of view of the possibility of causing harm, violation of the state of balance and ignoring. The analysis revealed the existence of a process of forming terminology, strengthening the scientific justification of the definitions of the definitions “danger”, “threat” and “risk”. Definitions force business entities to strengthen their protection and, accordingly become competitive in the market. In case of negative events top managers gain experience and this can be considered a starting point on the way to creating sustainable business activities since the identification of obstacles that stand in the way of sustainability of the enterprise must be constantly resolved. The ability of a business entity to recover from devastating events and adapt to changes is increasingly becoming a priority especially given that most of them face disruptions in the last period of time starting with the emergence of obstacles to the COVID-19 pandemic and the war in Ukraine.
Theoretical study of dangers, threats and risks in the economic security of the enterprise
Keywords: небезпека; загроза; ризик; економічна безпека підприємства; стабільність організації; danger; threat; risk; economic security of enterprises; stability of the organization; 338.24